2022
DOI: 10.3892/mco.2022.2549
|View full text |Cite
|
Sign up to set email alerts
|

A survey of feeding and swallowing function after free jejunal flap reconstruction in cases of head and neck cancer

Abstract: Reconstructive surgery using the free jejunum flap for locally advanced head and neck cancer is effective in preserving the swallowing function; however, it does not allow normal oral intake in all patients. A total of 47 patients underwent surgery at Nara Medical University between Jan 2010 and Dec 2019. The patients' ages ranged from 48 to 86 years. Sites were the hypopharynx (33 cases), larynx and cervical esophagus (5 cases each) and oropharynx (4 cases). Swallowing function was assessed using videofluorog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…27 In previous reports, preoperative RT was viewed as having an overwhelmingly negative impact on perioperative complications of FJT. 1,16,17,20,21,24,25 In this study, however, preoperative RT was not found to be a significant independent factor in perioperative complications or postoperative dysphagia, while postoperative RT was an independent factor for dysphagia. As for preoperative RT, perioperative complications may be affected by residual tissue and recipient vessels damaged by RT, but the disadvantage can be eliminated by resection of damaged tissue and replacement with a new FJ and accompanying mesentery, and also by selecting anastomotic vessels in good condition.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…27 In previous reports, preoperative RT was viewed as having an overwhelmingly negative impact on perioperative complications of FJT. 1,16,17,20,21,24,25 In this study, however, preoperative RT was not found to be a significant independent factor in perioperative complications or postoperative dysphagia, while postoperative RT was an independent factor for dysphagia. As for preoperative RT, perioperative complications may be affected by residual tissue and recipient vessels damaged by RT, but the disadvantage can be eliminated by resection of damaged tissue and replacement with a new FJ and accompanying mesentery, and also by selecting anastomotic vessels in good condition.…”
Section: Discussioncontrasting
confidence: 74%
“…Dysphagia after 6 months postoperatively: ischemia time (subject of the present study), BMI/history of neck surgery/radical neck dissection/postoperative RT/postoperative chemotherapy/recurrence within 1 year (significant trend in the univariate analysis), preoperative RT 1 20 25 (previous report).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation